Perancangan Interior Manchester United Fans Club di Surabaya - Rama Adinata (Intra, 2015)
Currently football has become the most popular sport in the world, it is directly proportional to the number of the fan club. Each fan club definitely needs a good place to gather it to share information, chat and even to watch the match together. Manchester United is the English football club that has the highest number of fan club in Indonesia. Therefore, in this thesis project a basecamp to accommodate the needs of the fan club Manchester United. The basecamp has several facilities such as Red Cafe, Room to watch the match, Mega Store, and the Information Center. The design of the basecamp of Manchester United  fan club is expected to be useful to accommodate all the needs of the fan club that has not been fully met.